PENINGKATAN MOTIVASI BELAJAR SKI MELALUI INTEGRASI GAME EDUKATIF BERBASIS ZEPQUIZ DAN MIND MAPPING - Yusrotul Widad; Ning Mukaromah (As-Sulthan Journal of Education, 2026)
Abstract : This study was motivated by the low learning motivation of tenth-grade students in the History of Islamic Culture (SKI) subject at MA Darul Ulum Karangpandan due to the use of conventional teaching methods that were monotonous and provided limited opportunities for active student participation. The study aimed to describe the improvement of students' learning motivation through the integration of the ZepQuiz educational game and Mind Mapping, as well as to identify the supporting and inhibiting factors in its implementation. A descriptive qualitative approach was employed, with data collected through observations, interviews, and documentation. Data were analyzed through data reduction, data presentation, and conclusion drawing, while source and technique triangulation were applied to ensure the trustworthiness of the findings. The results showed that the integration of ZepQuiz and Mind Mapping was implemented through systematic planning, implementation, and evaluation stages. This approach successfully enhanced students' learning motivation, as reflected in their increased enthusiasm, active participation, self-confidence, and engagement during the learning process. Students responded positively because the learning activities became more interesting, interactive, and easier to understand. Supporting factors included adequate learning facilities, teacher readiness, and students' enthusiasm, whereas the inhibiting factors were limited internet connectivity and differences in students' digital literacy. Abstrak : Penelitian ini dilatarbelakangi oleh rendahnya motivasi belajar siswa pada mata pelajaran Sejarah Kebudayaan Islam (SKI) di kelas X MA Darul Ulum Karangpandan akibat penggunaan metode pembelajaran konvensional yang monoton dan kurang melibatkan siswa secara aktif. Penelitian ini bertujuan untuk mendeskripsikan peningkatan motivasi belajar siswa melalui integrasi game edukatif berbasis ZepQuiz dan Mind Mapping, serta mengidentifikasi faktor pendukung dan penghambat dalam penerapannya. Penelitian menggunakan pendekatan kualitatif deskriptif dengan teknik pengumpulan data melalui observasi, wawancara, dan dokumentasi. Analisis data dilakukan melalui reduksi data, penyajian data, dan penarikan kesimpulan dengan triangulasi sumber dan teknik untuk menguji keabsahan data. Hasil penelitian menunjukkan bahwa integrasi ZepQuiz dan Mind Mapping dilaksanakan melalui tahap perencanaan, pelaksanaan, dan evaluasi yang terstruktur. Penerapan kedua metode ini mampu meningkatkan motivasi belajar siswa yang terlihat dari meningkatnya antusiasme, keaktifan, rasa percaya diri, dan keterlibatan siswa selama pembelajaran. Siswa memberikan respon positif karena pembelajaran menjadi lebih menarik, interaktif, dan mudah dipahami. Faktor pendukung meliputi fasilitas pembelajaran yang memadai, kesiapan guru, dan antusiasme siswa, sedangkan faktor penghambat meliputi keterbatasan jaringan internet dan perbedaan kemampuan siswa dalam menggunakan media digital.